A case of secondary syphilis presenting on the oral mucosa: A case report. Issue 3 (9th September 2019) - Harada, Yusei; Amekawa, Shigeki; Takubo, Kazuko; Otsuki, Kazuma; Kawasaki, Makoto; Tamura, Takayuki; Fujii, Nobuyuki; Kodani, Isamu
Abstract: Syphilis is a sexually transmitted disease caused by Treponema pallidum. We report a case of secondary syphilis originating in the oral mucosa. The patient was a 58‐year‐old man who visited our hospital at May 2009. Clinical examination revealed a mass at the right angle of the mouth with a white mass on the tip of the tongue and an indurated ulcer on the left border of the tongue. Magnetic resonance imaging revealed multiple swollen lymph nodes in the bilateral submandibular glands, as well as in the bilateral deep cervical and supraclavicular lymph nodes. Serological examination revealed elevated rapid plasma reagin (RPR) (titer, 1:32) and Fluorescent treponemal antibody absorption test (2+) values. Consequently, the mass at the right angle of the mouth, the white patch on the tip of the tongue, and the ulcer on the left border of the tongue were diagnosed as secondary syphilis. Oral amoxicillin 1500 mg/d was administered for 4 weeks. The oral lesions improved after 20 days of treatment and the RPR titer had improved to 1:2 after 5 months of treatment.